Policy Assessment in the OECD : Lessons for Chile - World Bank (World Bank, Washington, DC, 2020)
Chile is well-advanced in the field of program and project evaluation, with adequate institutions and procedures in place, and has achieved a very high standard by any international comparison. DIPRES has established a system of evaluations of sound quality. This system promotes the utilization of evaluation results in management decisions, including budget decision. The outsourcing of evaluations guarantees technical and political independence of program and project evaluations, while increasing their credibility. On the other hand, policy evaluation in Chile is mainly an ad-hoc and spontaneous activity, with no definite procedures or standards. Regardless of the quality of those sporadic evaluations, the fact remains that no one is responsible for the selection, methods, implementation, financing, and utilization of the results of policy evaluations. This report will focus on developing a strategy and instruments for further institutionalizing public policy assessment in Chile. The first chapter discusses definitions and concepts related to the public policy process and describes the scope of this report. Chapter second examines the policy processes of six Organization for Economic Cooperation and Development (OECD) countries, including federal countries such as Canada and the United States (U.S.) and unitary countries similar to Chile. Chapter third takes the OECD context as background to analyze Chile’s own policy process and lays out challenges to improving the policy process in Chile. Chapter fourth builds on the previous analysis to offer a number of possible directions Chile can take to achieve its goal of strengthening public policy assessment.